QSAR, Docking, Screening, Toxicity, And Pharmacokinetic Profile Of 4-Amino-1-Hydroxy-2-Oxo-1,8-Naphthyridine-3-Carboxamide Derivatives As Antihiv-1 Integrase In Silico - Hardiyanti Syarif; Jumasni Adnan; Putri Juanti; Nursalam Hamzah; Nur Syamsi Dhuha (Program Studi Farmasi Universitas Mandala Waluya, 2026)
Integrase is an important molecular target for HIV transmission. The function of integrase inhibitors in overcoming wild-type mutant resistance provides new advances in research. This study aimed to determine the physicochemical properties of 4-amino-1-hydroxy-2-oxo-1,8-naphthyridine-3-carboxamide derivative compounds on integrase enzyme inhibitory activity for HIV-1 treatment based on the QSAR equation, to determine the ligand-receptor hydrogen bond interaction through molecular relationships, to identify the features that drive the selectivity and activity of compounds targeting the integrase enzyme, to conduct virtual screening, and to predict toxicity and pharmacokinetic profiles in silico. QSAR descriptors, molecular docking, pharmacophore features, and virtual screening were calculated with MOE 2009.10 and statistical analysis with the SPSS Statistics 17.0 program. Then pharmacophore docking was performed on two selected compounds from the ZINC database, toxicity tests were performed with Toxtree and AdmetSAR, and pharmacokinetic profiles were determined with PreADMET. The QSAR model showed the best equation: Log (1/IC50) = -1.72 -0.983235703 Mr +0.146570594 AM1_Dipole +0.0019 AM1-HF -0.0895 log S +0.0000 AM1_Eele. The best scoring value in compound 5e is -78.5465. Both compounds have been predicted for suitability and safety, as well as their pharmacokinetic profiles.